The refusal of politics - Dubreuil, Laurent (Incitements., 2016)
Dubreuil provocatively proposes an extremist rethinking of the limits of politics ́⁰₃ toward a break from politics, the political and policies. He calls for a refusal of politics, suggesting a form of apolitics that would make our lives more liveable. The first chapter situates the refusal of politics in relation to different contemporary theoretical attempts to renew politics, and makes the case for a greater rupture. The second moment takes up what is liveable in life by way of apolitical experience, in contrast to appropriations of the collective, including a discussion of the arts. Finally, Laurent Dubreuil draws up an incomplete inventory of means, forms of existence ́⁰₃ often frail and fleeting ́⁰₃ that make an exit toward atopia.